2011
DOI: 10.3892/or.2011.1356
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of discoidin domain receptor 2 in A375 human melanoma cells reduces its experimental liver metastasis ability

Abstract: Abstract. Discoidin domain receptors (DDr1 and DDr2) are tyrosine kinase receptors for fibrillar collagen implicated in postnatal development, tissue repair, and primary and metastatic cancer progression. While DDR1 has been described in tumor cells, DDR2 has been localized in the tumor stroma, but its presence in the tumor cells remains unknown. The aim of this study was to elucidate the role of DDR2 signaling in tumor cells during hepatic metastasis progression. DDR2 expression and phosphorylation in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Several studies have demonstrated that DDR2 overexpression and signaling activation in breast cancer cells promotes tumor progression, sparking interest in DDR2 tyrosine kinase as a target for the treatment of breast and other malignancies (Badiola et al, 2011; Kim et al, 2015; Valiathan et al, 2012; Zhang et al, 2013). While no DDR2 mutations were identified in breast cancer, our lab and other investigators found that DDR2 is overexpressed in over 50% of invasive breast carcinomas compared to none of the normal breast epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that DDR2 overexpression and signaling activation in breast cancer cells promotes tumor progression, sparking interest in DDR2 tyrosine kinase as a target for the treatment of breast and other malignancies (Badiola et al, 2011; Kim et al, 2015; Valiathan et al, 2012; Zhang et al, 2013). While no DDR2 mutations were identified in breast cancer, our lab and other investigators found that DDR2 is overexpressed in over 50% of invasive breast carcinomas compared to none of the normal breast epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, DDR1 is expressed in epithelial cells and DDR2 only in mesenchymal stromal cells, where it regulates ECM synthesis and participates in wound healing (Alves et al, 1995; Olaso et al, 2002; Valiathan et al, 2012). Pathologic DDR2 upregulation has been reported in several human malignancies including breast cancer where it is significantly associated with worse survival (Badiola et al, 2011; Barcellos-Hoff et al, 2013; Kim et al, 2015; Toy et al, 2015; Valiathan et al, 2012; Zhang et al, 2013). In breast cancer cells, DDR2 was shown to maintain Snail1 activity and an epithelial to mesenchymal transition (EMT) phenotype (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both DDR1 and DDR2 can exhibit pro- [131,30,79,132,101,133,118,128,69,134,87] and anti- [135,126,94,129,136] proliferative activities in a cell type and context-dependent manner. However, the mechanisms by which each DDR regulates cell proliferation are unknown but are likely to require kinase activity [79].…”
Section: Function Of Ddrs In Normal and Cancer Tissuesmentioning
confidence: 99%
“…DDR2 is involved in several key roles including proliferation, migration, adhesion and remodeling of the extracellular matrix [48], [49], and is expressed in stromal cells while a relative, DDR1 , is expressed in epithelial cells [73]. In vitro studies of hepatic stellate cells and skin fibroblasts have demonstrated a drop in cell proliferation and migration in the absence of DDR2 [74][76]. Nude mice that received intrasplenic injections of human melanoma cell line A375 with stably silenced DDR2 had fewer hepatic metastasis than mice receiving mock transfected cells [74].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of hepatic stellate cells and skin fibroblasts have demonstrated a drop in cell proliferation and migration in the absence of DDR2 [74][76]. Nude mice that received intrasplenic injections of human melanoma cell line A375 with stably silenced DDR2 had fewer hepatic metastasis than mice receiving mock transfected cells [74]. In contrast DDR2 −/− mice that received intrasplenic injection of murine colon adenocarcinoma cell line MCA38 had more hepatic metastasis than equivalently treated DDR2 +/+ mice [77].…”
Section: Discussionmentioning
confidence: 99%